Cultural theory and popular culture a reader - Storey, John 1950- (London New York Routledge, 2019)
"The fifth edition of John Storey's successful Cultural Theory and Popular Culture Reader is an essential companion volume to Cultural Theory and Popular Culture: An Introduction, now in its eighth edition. The reader offers students the opportunity to experience first-hand the theorists and critics discussed in Cultural Theory and Popular Culture: An Introduction through crucial articles and essays spanning over a hundred years of cultural theory. It can be used both in conjunction with and independently of the textbook. Taken as a whole, this book provides a theoretical, analytical and historical introduction to the study of popular culture and provides key primary coverage of fundamental issues in cultural studies. This edition includes: - a new section on Class, as well as additional readings on Sexuality and Gender. - fully revised general and section introductions from the editor, contextualising and linking the readings with key issues from the textbook - fully updated bibliography The new edition is essential reading for undergraduate and postgraduate students of cultural studies, media studies, communication studies, the sociology of culture, popular culture and other related subjects"--
Introduction : the study of popular culture and cultural studies -- Culture and anarchy / Matthew Arnold -- Mass civilisation and minority culture / F.R. Leavis -- The full rich life & the newer mass art : sex in shiny packets / Richard Hoggart -- The analysis of culture / Raymond Williams -- Preface from the making of the English woking class / E.P. Thompson -- The young audience / Stuart Hall and Paddy Whannel -- Ruling class and ruling ideas / Karl Marx and Frederick Engles -- Base and superstructure / Karl Marx -- Letter to Joseph Bloch / Frederick Engels -- On popular music / Theodor W. Adornon -- Hegemony, intellectuals and the state / Antonio Gramsci -- Popular culture and the 'turn of Gramsci' / Tony Bennett -- Pleasurable negotiations / Christine Gledhill -- The rediscovery of 'ideology' : return of the repressed in media studies / Stuart Hall -- Post-Marxism without apologies / Ernesto Laclau with Chantal Mouffe -- Class / Raymond Williams -- Short extract from the Communist manifesto / Karl Marx and Frederick Engels -- Distinction & the aristocracy of culture / Pierre Bourdieu -- The upper classes : visibility, adaptability and change / Anita Biressi and Heather Nunn -- Meritocracy as plutocracy : the marketising of "equality" under neoliberalism / Jo Littler -- Feminist approaches to popular culture : giving patriarchy its due / Lana F. Rakow -- Dallas and the ideology of mass culture / Ien Ang -- Reading the romance / Janice Radway -- Imitation and gender insubordination / Judith Butler -- What a man's gotta do / Anthony Easthope -- Post-feminism and popular culture / Angela McRobbie -- Blurred lines : the queer world of bad girls / Vicky Ball -- Post-postfeminism? : new feminist visibilities in postfeminist times / Rosalind Gill -- The dream-work / Sigmund Freud -- The mirror stage / Jacques Lacan -- Myth today / Roland Barthes -- The structure of myth & the structure of the Western film / Will Wright -- Jules Verne : the faulty narrative / Pierre Macherey -- Ideology and ideological state apparatuses / Louis Althusser -- Method / Michel Foucault -- Feminism & the principle of poststructuralism / Chris Weedon -- From reality to the real / Slavoj Zizek -- 'Get up, get into it and get involved' - soul, civil rights and black power / Paul Gilroy -- The color purple : black women and cultural readers / Jacqueline Bobo -- What is this 'black' in black popular culture? / Stuart Hall -- Black postmodernist practices / Cornel West (interviewed by Anders Stephanson) -- Postmodern blackness / bell hooks -- The precession of simulacra / Jean Baudrillard -- From here to modernity : feminism and postmodernism / Barbara Creed -- Feminism, reading, postmodernism / Meaghan Morris -- Postmodernism and 'the other side' / Dick Hebige -- Fashion and postmodernism / Elizabeth Wilson -- Genericity in the nineties / Jim Collins -- Notes on deconstructing 'the popular' / Stuart Hall -- Cultural entrepreneurship in nineteenth-century Boston : the creation of an organizational base for high culture in America / Paul Dimaggio -- Cultural production / Terry Lovell -- The practice of everyday life / Michel De Certeau -- The popular economy / John Fiske -- Feminist desire and female pleasure / Ien Ang.
Includes bibliographical references and index.
Keywords: Popular culture; Culture -- History; Popular culture -- Philosophy